Case report: Disseminated herpes simplex virus 1 infection and hemophagocytic lymphohistiocytosis after immunomodulatory therapy in a patient with coronavirus disease 2019 - Mazzotta, Elvio; Fiorda Diaz, Juan; Echeverria-Villalobos, Marco; Eisinger, Gregory; Sprauer, Sarah; Singha, Arindam; Lyaker, Michael R. (Frontiers in Medicine, 2022)
Corticosteroid and immunomodulatory therapies are widely used to treat patients with severe coronavirus disease 2019 (COVID-19). Janus kinase (JAK) inhibitors such as tofacitinib have been recently studied as adjutants in the treatment of COVID-19. Although immunomodulatory therapies may be linked to decreased mortality rates in the acute phase, subsequent severe infectious complications may result from them. We describe a case of a multiorgan system failure secondary to disseminated herpes simplex virus 1 (HSV-1) infection and hemophagocytic lymphohistiocytosis (HLH) following treatment with tofacitinib and high-dose dexamethasone therapy for severe COVID-19. Early diagnosis and treatment of these life-threatening conditions may have a significant impact on COVID-19 patients’ outcomes.